2008
DOI: 10.5694/j.1326-5377.2008.tb02117.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of sexually transmitted infections on the Anangu Pitjantjatjara Yankunytjatjara Lands: results of a comprehensive control program

Abstract: Objective: To assess the impact of a long‐term comprehensive control program for sexually transmitted infections (STIs) in remote Aboriginal communities in Central Australia, and to investigate a recent rise in gonorrhoea prevalence. Design: STI prevalence was determined from annual, cross‐sectional, population‐wide, age‐based screening, 1996–2006. During 2006, gonococcal isolates were obtained by on‐site culture and tested for antimicrobial susceptibility. Setting: Six remote clinics on the Anangu Pitjantjatj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 11 publications
2
35
0
Order By: Relevance
“…The increasing use of NAAT for diagnosis means susceptibility profiles are often not available. In remote areas of Australia where the prevalence of penicillin-resistant N. gonorrhoeae is low, as was found in this study,26 the use of a penicillin-based oral regime following initial use of a third generation cephalosporin may therefore be reasonable and appeared to reflect local practice seen here.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The increasing use of NAAT for diagnosis means susceptibility profiles are often not available. In remote areas of Australia where the prevalence of penicillin-resistant N. gonorrhoeae is low, as was found in this study,26 the use of a penicillin-based oral regime following initial use of a third generation cephalosporin may therefore be reasonable and appeared to reflect local practice seen here.…”
Section: Discussionsupporting
confidence: 57%
“…This is of particular concern given DGI has previously been reported as the first presenting manifestation of HIV infection 23–25. Furthermore, there is also the tendency for different STIs to cluster in one individual15 16 26 and, as such, a cluster of STIs may alter treatment guidelines. Thus, anyone suspected of DGI should also have appropriate specimens collected and tested for other STIs and blood borne viruses, even if genitourinary symptoms are not present.…”
Section: Discussionmentioning
confidence: 99%
“…Just one study reported prevalence estimates over time [69,70], finding that prevalence decreased for both men and women over the first study period (1998–2000), from 8.8% to 7.2% in men, and from 9.1% to 7.2% in women. However, this was linked to the introduction of a sexual health intervention, and the falls were not significant [69].…”
Section: Resultsmentioning
confidence: 99%
“…Staff score their health service on an 11-point scale in each area, with an aim of improving areas at subsequent annual assessments. The areas cover the fundamental components of a comprehensive sexual health program identified for the remote primary health care setting [30]. …”
Section: Methodsmentioning
confidence: 99%